The Battle of Russia, Part 1 - Capra, Frank (United States, 1946)
The fifth in the "Why We Fight" series of seven army information films, "Battle for Russia" gives the brief history of Russia and the wars fought on her homeland. Then it moves to WWII and the invasion by Nazi forces, using newsreels of the actual fighting. The Nazis are victorious at Moscow and Leningrad but, like Napoleon's troops, are utterly defeated at the battle of Stalingrad.
Keywords: Documentary films